Biomedicine in an Unstable Place : Infrastructure and Personhood in a Papua New Guinean Hospital - Street, Alice (Book collections on Project MUSE., 2014)
This ethnography shows how the struggle to practice clinical medicine in a resource-strapped public hospital in Papua New Guinea is complicated by the attempts of doctors, nurses, and patients to make themselves visible to others-kin, clinical experts, global scientists, politicians, and international development workers-as socially recognizable and valuable persons.